Efficacy and safety of a novel monopolar radiofrequency device with a continuous water-cooling system in patients with age-related facial volume loss - Seungwon Lee; Jihyun Hyun; Yeonwoo Shin; Boncheol Leo Goo (Taylor & Francis Group, 2024)
Background Esthetic radiofrequency (RF) technology has much attracted public attention with the increasing demand for skin rejuvenation. A continuous water cooling-based monopolar RF (MRF) device was designed for the first time to protect the epidermis and maximize clinical outcomes.Objective Assess the efficacy and safety of the proposed MRF device in patients with mild-to-moderate sunken cheeks and jawline laxity.Methods Twenty-one patients underwent a single session of MRF treatment. Quantitative analysis was performed using a 3D imaging technique. Postprocedural clinical improvements were assessed with the Merz Scale. Regarding safety, adverse events (AEs), thermal sensation (TS) and pain intensity were explored. Patient satisfaction was surveyed with the Self-Assessment Questionnaire (SAQ).Results The follow-up investigation demonstrated that facial volume increased across the cheek and jawline, with lifting effects throughout the treatment area. The Merz Scale assessment revealed that sunken cheeks, sagging jawlines and wrinkles were markedly improved. In addition, there were transient AEs, mild TS and moderate pain. In SAQ, 81% patients were satisfied with the procedure.Conclusions This study provided quantitative evidence for postprocedural volumetric increases along with enhanced lifting effects, strongly implying that the proposed MRF device can be an attractive option for improving facial skin volume loss and laxity.